Plant biology: building barriers... in roots - van Wangenheim, Daniel; Goh, Tatsuaki; Dietrich, Daniela; Bennett, Malcolm J. (Elsevier (Cell Press), 2017)
The Casparian strip is an important barrier regulating water and nutrient uptake into root tissues. New research reveals two peptide signals and their co-receptors play critical roles patterning and maintaining barrier integrity.